IMPLEMENTASI PNEUMATIK PADA RANCANG BANGUN PEMBERIAN PAKAN PADA TERNAK AYAM SECARA OTOMATIS BERBASIS PROGRAMMABLE LOGIC CONTROLLER - Urai, Aristevani; Damayanti, Eva (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i1.965, 2025)
In an industry with increasingly modern technology, an automatic control system is needed that can support the industrial production system to make it more stable and optimal. This research aims to design and implement an automatic feeding system for chickens using Programmable Logic Controller (PLC) technology and a pneumatic system. The background to this research is based on the importance of efficiency and effectiveness in chicken farming practices, especially in feeding which is a crucial factor for chicken growth and productivity. Using manual methods in feeding is still a challenge, especially for breeders with large chicken populations, because it can cause non-uniformity, waste of time and increase operational costs. It is hoped that the implementation of automation technology in the feeding system can overcome this problem by optimizing feed distribution and reducing manual intervention. The system developed in this research uses a PLC (Programmable Logic Controller) to regulate the schedule and amount of feed given, while the pneumatic system is used as an actuator to open and close the feed door quickly and reliably. This research uses a qualitative method that focuses on in-depth observations to produce a more comprehensive study of the design. Test results show that this system is able to work efficiently and stably, ensuring timely distribution of feed at 07:00 and 17:00 and providing feed in quantities appropriate to livestock needs. Thus, it is hoped that the implementation of this technology can increase the productivity of chicken farms, reduce the farmer's workload, and ensure that each chicken gets optimal feed.